Penggunaan Obat Antiinflamasi Untuk Penyakit RheumatoidArthritis Pada Pasien Rawat Jalan Di RSUDManokwariTahun 2021 - MARASABESSY, HADIJA (Poltekkes Kemenkes Kendari, 2023)
Rheumatoid Arthritis is an autoimmune disease in the form of inflammatory arthritis, a person suffering from Rheumatoid Arthritis disease experiences symptoms of pain in the synovial joints. This type of research is quantitative with a cross sectional approach. The population in this study is 30 medical record data, this study was carried out in the RM room of the Manokwari Hospital on January 7 to January 15, 2022, the instrument used was RM patients with Rheumatoid Arthitis, the analysis used univariate data analysis described and presented in the form of tables and percentages. The results of this study showed that most patients diagnosed with Rheumatoid Arthritis were 23 women (76.7%). The age range of most diagnosed Rheumatoid Arthritis 65 years 10 patients (33%). Types of drugs that are widely used are generic drugs 30 (100%). The classification of NSAIDs that are widely used is COX-2 NSAIDs, there are 19 drugs meloxicam (63.3%). The duration of drug administration was 14 days with meloxicam (43.3%). The dose of NSAID used was 1x15mg (43.3%). The conclusion is that the female gender suffers the most from Rheumatoid Arthritis, the age most affected by Rheumatoid Arthritis is 65 years, the generic drug used, the class of drug used is COX-2, given for 14 days, the dose used is 1x15mg. It is hoped that there will be education for health workers at the Manokwari Hospital related to the pattern of using anti-inflammatory drugs for Rheumatoid Arthritis so that appropriate therapy is obtained. Keywords: Rheumatoid Arthritis, Anti-Inflammation, Manokwari Hospital